Clinical, histological, and molecular risk factors for cancer recurrence in patients with stage II colon cancer. Issue 12 (December 2016) - Touchefeu, Yann; Provost-Dewitte, Marie; Lecomte, Thierry; Morel, Alain; Valo, Isabelle; Mosnier, Jean-François; Bossard, Céline; Eugène, Juliette; Duchalais, Emilie; Chetritt, Jérôme; Guyetant, Serge; Bézieau, Stéphane; et al.
Abstract : Introduction: The assessment of risk factors of cancer recurrence in patients with stage II colon cancer (CC) is crucial. Our aim was to study the clinical, histological, and molecular features associated with 3-year disease-free survival in a series of consecutive patients with stage II CC treated in three regional digestive oncology centers. Methods: Clinical and histological data of all patients after curative surgery for stage II CC, treated from 2001 until 2009, were collected retrospectively. Histological samples were obtained and tested prospectively for microsatellite instability using fluorescent PCR amplification. Cox proportional hazards regression models were used to calculate P values, hazard ratios (HRs), and 95% confidence intervals (CIs). Results: Among 195 patients studied, 22 (11%) had disease recurrence during the 3-year period following diagnosis. On multivariate analysis, only low number of lymph nodes (HR=3.81, 95% CI: 1.19–12.19, P =0.02) and T4 status (HR=5.49, 95% CI: 1.06–28.43, P =0.04) were associated significantly with an increased risk of relapse. Conclusion: In this series of stage II CC patients, only T4 status and low number of lymph nodes were independent risk factors for poor 3-year disease-free survival, suggesting that patients with these features should be considered for adjuvant chemotherapy.